A Fast Approach to Bimatrix Games with Intuitionistic Fuzzy Payoffs. (14th August 2014) - Fan, Min; Zou, Ping; Li, Shao-Rong; Wu, Chin-Chia
Abstract : The aim of this paper is to develop an effective method for solving bimatrix games with payoffs of intuitionistic fuzzy value. Firstly, bimatrix game model with intuitionistic fuzzy payoffs (IFPBiG) was put forward. Secondly, two kinds of nonlinear programming algorithms were discussed with the Nash equilibrium of IFPBiG. Thirdly, Nash equilibrium of the algorithm was proved by the fixed point theory and the algorithm was simplified by linear programming methods. Finally, an example was solved through Matlab; it showed the validity, applicability, and superiority.